Upaya meningkatkan aktivitas dan hasil belajar matematika Pada materi operasi hitung pecahan melalui penerapan model pembelajaran Kooperatif tipe Two stay Two Stray Siswa Kelas V MIN 8 Aceh Barat Daya - Erliana, Erliana (Universitas Serambi Mekkah, 2020)
The purpose of this study was to improve mathematics learning activities and outcomes in fraction counting operations material through a two stay two stray cooperative learning model for students in class V MIN 8 Aceh Barat Daya Academic Year 2019/2020. The model used in this study is the two stay two stray cooperative learning model. The subjects of this study were fifth grade students MIN 8 Southwest Aceh. The number of students is 35 students with a total of 14 male students and 21 female students. This research was conducted in the 2018/2019 school year within a period of 3 months, from September to November 2018 in odd semester. The methodology of this research is Classroom Action Research (CAR) consists of two cycles and each cycle consists of two meetings. Each cycle consists of planning, implementing, observing and reflecting. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection tech-nique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by looking at student activities in the learn-ing process. Data were analyzed by means of percentage statistics. The results showed that there was an increase in student learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Completeness of student learning outcomes has increased from 39.13% in pre-study increased to 65.21% in the first cycle and increased to 86.95% in the second cycle. The application of the two stay two stray type of cooperative learning model can improve the activities and learning outcomes of students in mathematics in the calculation operations of fractions of students in grade V MIN 8 Aceh Barat Daya Academic Year 2019/2020.